2016
DOI: 10.1142/s1793545816300056
|View full text |Cite
|
Sign up to set email alerts
|

The role of surface functionalization of silica nanoparticles for bioimaging

Abstract: Among the several types of inorganic nanoparticles available, silica nanoparticles (SNP) have earned their relevance in biological applications namely, as bioimaging agents. In fact,°uorescent SNP (FSNP) have been explored in this¯eld as protective nanocarriers, overcoming some limitations presented by conventional organic dyes such as high photobleaching rates. A crucial aspect on the use of°uorescent SNP relates to their surface properties, since it determines the extent of interaction between nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 133 publications
0
23
0
Order By: Relevance
“…This technique allows characterization of disease at multiple spatial scales. For example, SPIONs labeled with Cy5.5, functionalized silica nanoparticles or FITC-conjugated magnetite nanoparticles and many other similar combinations were utilized for biomedical imaging applications [21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…This technique allows characterization of disease at multiple spatial scales. For example, SPIONs labeled with Cy5.5, functionalized silica nanoparticles or FITC-conjugated magnetite nanoparticles and many other similar combinations were utilized for biomedical imaging applications [21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…Silicon dioxide nanoparticles (SiO 2 NPs) are engineered nanomaterials that can be categorized as solid, porous, or mesoporous (Esim et al, 2019). The ease of modification of the surface chemistry of SiO 2 NPs has been widely exploited to control their interactions with biological systems used for drug delivery and to serve their purpose related to the remediation of environmental contaminants (Farrukh et al, 2014;Gomes et al, 2016;Mao et al, 2020). It has been reported that surface modification of SiO 2 NPs enhances colloidal stability, biocompatibility, and target specificity as well as improving cellular uptake, all of which are necessary components of drug delivery and bioimaging applications (Besic Gyenge et al, 2011;Kralj et al, 2012;Liberman et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…With the nanotechnology emergence, a wide variety of silica nanostructures have been produced which have shown great potential for various applications [5][6][7][8]. Silica nanoparticles (SiNPs) are the most studied, and their applications include adsorption process, bioimaging, catalysis, polymer nanocomposites, biosensors and drug delivery [9][10][11][12][13]. Currently, mesoporous SiNPs (MSNPs) alone or in the combined form are widely used to design drug delivery systems for biomedical applications [13].…”
Section: Introductionmentioning
confidence: 99%